DEFINING THE PROBLEM OF ILLEGAL FOREIGN WORKERS AS WICKED PROBLEMS - Sri Kuncoro Bawono (Polteknik Imigrasi, 2018)
The issue of Illegal foreign worker existence in Indonesia has attracted the government to react to this problem since this issue has made a restlessness in public. The existence of the illegal foreign workers considered could bring threats to the national security. Accordingly, the Directorate General of Immigration has tried to overcome this problem by strengthening the Immigration Law Enforcement; However, this effort seems do not really solve the problem. This is because the intricacy of the problem that makes the solution which implemented did not bring an intended outcome. Therefore, to find the appropriate solution, this problem should be framed differently by defining this as a wicked problem. This research will describe the complexity, the uncertainty, and the value diversity in this problem that construct this problem as a wicked problem.